Pro12Ala Polymorphism on the PPARγ2 Gene and Weight Loss After Aerobic Training: A Randomized Controlled Trial - Cardoso, Glêbia Alexa; Persuhn, Darlene Camati; Ribeiro, Mateus Duarte; de Sousa, Bruno Rafael Virgínio; Sena, Klécia de Farias; de Almeida, Antônio Eduardo Monteiro; Modesto-Filho, João; da Silva, Raquel Suelen Brito; Silva, Alexandre Sérgio (Frontiers in Physiology, 2020)
The objective of this study was to verify the influence of the Pro12Ala polymorphism of the PPARγ2 gene in response of a training program on the body composition. Sixty-nine previously inactive men and women (32.8 ± 8.2 years) were genotyped and underwent a 12-week aerobic (running/walking) training program (3–5 sessions, 40 – 60 min per session, and intensity between the aerobic and anaerobic threshold) (experimental group n = 53) or were part of the control group (n = 16). They were tested for aerobic capacity (ergospirometry), body composition (DXA), abdomen, waist and hip circumferences and nutritional assessment before and 48 h after the experimental protocol. Two-way repeated measures ANOVA test was used to verify possible differences in variables between the experimental vs. control groups or Pro/Pro vs. Pro/Ala groups, and the Chi-squared test was used to verify the distribution of responders and non-responders according to genotype (p < 0.05). Frequencies of 75.5% Pro/Pro (n = 40) and 24.5% Pro/Ala (n = 13) were found, without any occurrence of the recessive homozygote. Body fat reduction was initially confirmed compared to a control group which did not exercise (n = 16; 29.1 ± 8.8 years), so that the exercise group obtained a reduction of −1.3 kg vs. −0.3 kg in the control group (p = 0.03). When they were divided by genotype, there were significant changes in fat mass (−1.3 ± 2.1 kg; p = 0.00), lean mass (0.6 ± 1.5 kg; p = 0.02), fat percentage (−1.3 ± 1.6; p = 0.00), waist circumference (−2.2 ± 2.9 cm; p = 0.00), abdomen circumference (−3.3 ± 3.6 cm; p = 0.00) and hip circumference (−2.7 ± 2.7 cm; p = 0.00) for Pro/Pro genotypes; and fat mass (−1.1 ± 1.7 kg; p = 0.04), fat percentage (−0.9 ± 1.5; p = 0.04), abdomen circumference (−3.9 ± 3.5 cm; p = 0.00) and hip circumference (−1.8 ± 1.8 cm; p = 0.00) for Pro/Ala genotypes, without any group interaction differences. The Chi squared test revealed no differences in the distribution of responders or non-responders according to genotype. It is concluded that an aerobic training program promotes weight loss, but the Pro12Ala polymorphism in the PPARγ2 gene does not influence the variability of aerobic-induced exercise weight loss.